miRNA miR-21 Is Largely Dispensable for Intrathymic T-Cell Development - Kunze-Schumacher, Heike; Winter, Samantha J.; Imelmann, Esther; Krueger, Andreas (Frontiers in Immunology, 2018)
Development of T cells in the thymus is tightly controlled to continually produce functional, but not autoreactive, T cells. miRNAs provide a layer of post-transcriptional gene regulation to this process, but the role of many individual miRNAs in T-cell development remains unclear. miR-21 is prominently expressed in immature thymocytes followed by a steep decline in more mature cells. We hypothesized that such a dynamic expression was indicative of a regulatory function in intrathymic T-cell development. To test this hypothesis, we analyzed T-cell development in miR-21-deficient mice at steady state and under competitive conditions in mixed bone-marrow chimeras. We complemented analysis of knock-out animals by employing over-expression in vivo. Finally, we assessed miR-21 function in negative selection in vivo as well as differentiation in co-cultures. Together, these experiments revealed that miR-21 is largely dispensable for physiologic T-cell development. Given that miR-21 has been implicated in regulation of cellular stress responses, we assessed a potential role of miR-21 in endogenous regeneration of the thymus after sublethal irradiation. Again, miR-21 was completely dispensable in this process. We concluded that, despite prominent and highly dynamic expression in thymocytes, miR-21 expression was not required for physiologic T-cell development or endogenous regeneration.